Rancang Bangun Mesin CNC Router Berbasis Arduino - Sudarno; Martono; Sholih Mauladin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2016)
CNC Router machine is a cutting machines based computer that can run the process automatically on a wide variety of materials based commands that have been programmed into the software. CNC Router design aims design and create a CNC Router machine with hardware and software that is easy to use and come in the market. Software used in the operation of the machine is Grbl Controller, while for the microcontroller use of ATMega328 from Arduino Uno R3 board. Supported also by the Arduino Software and X-Loader, as well as making the program (design) using Mastercam Mill 9. The result of design CNC Router machine is used for testing in the manufacture of finished object in the form of a 2D image on paper media, and can be developed for future learning media.